Anxiety in the emergency medical practice - its psychiatric and somatic origin, comorbidities, behavior and treatment - Silvia Sarakostova; Diyana Pantileeva; Dancho Dilkov; Niya Semerdzhieva; Mariya Chaneva; Stefka Ivanova; Ventseslava Atanasova; Petar Atanasov; Diana Rangelova (Pensoft Publishers, 2024)
Anxiety conditions and disorders are common in the general population, and patients suffering from them often seek the services of emergency departments. Anxiety is a psychopathological symptom that accompanies not only psychiatric conditions, but a wide range of somatic diseases, and a combination of both. The biochemical and pathophysiological mechanisms of psychosomatic interrelationship and comorbidity are complex and multi-layered. Thus, diagnosing the root cause of anxiety is a clinical challenge. Early, and on time, recognition of an anxiety disorder helps to avoid unnecessary investigations, ensures correct treatment and saves hospital resources. Careful use of medications, psychoeducation and referral to a specialist improves patient outcome with this potentially debilitating disease. In this article, the authors aim to present in a synthesized form the main epidemiological data on the prevalence of anxiety symptoms and disorders, anatomical localization and biochemical mechanisms and relationships in the pathogenesis of anxiety symptoms, as well as to derive the main guidelines for recognizing and differentiating clinicopathological constellations in somatic conditions in emergency medical practice. Materials and methods. Existing published studies from an international database, related to the subject of the article, have been thoroughly studied. Results. Anxiety symptoms, in particular panic attacks and disorders, are widespread in primary care and occupy a significant part of the work process, especially at times of peak loads, natural disasters and situations of mass traumatism. Conclusions. Timely training and good preparation for recognition and adequate assessment of anxiety conditions in primary and emergency medical care significantly shorten the therapeutic route of patients. They receive competent help on time, and the cost of their treatment is significantly reduced. Discussion. Modern medical science, including psychiatric, offers advanced drug and non-drug methods for the treatment and prevention of anxiety conditions and disorders.